DESIGN AND DEVELOPMENT OF SOLID DISPERSION SYSTEM OF ZOLMITRIPTAN - A. Mittal1, Mohd. Zakir Khan2, *Bankim Chandra Nandy1, A. K. Gupta1, (Journal of Biomedical and Pharmaceutical Research, 2013)
Zolmitriptan is a potent anti-migraine drug.  The bioavailability of Zolmitriptan is about 40% via oral dosage forms and problem arises from its low water solubility and dissolution rate. The present study deals with formulation of solid dispersions of variying ratios of Zolmitriptan (ZMP) and urea or poly vinyl pyrrolidone K-30 (PVP K-30) or PEG-6000 were prepared by hot melt and solvent evaporation method in an effort to increase the dissolution rate as well as bioavailability of the drug. The properties of solid dispersions were characterized by FTIR , XRD and DSC. FTIR  analysis demonstrated the presence of intramolecular hydrogen bonds between Zolmitriptan and PVP K-30 in solid dispersions. Dissolution studies indicated that the dissolution rate were markedly increased in these solid dispersions systems compared with those in physical mixtures. The increase in dissolution rate strongly depended on the type, ratios of drug to carriers and selection of the method of preparations of solid dispersions. The solid dispersions compound prepared in the ratio of 1:5 by the PVP K-30 showed the higest improvement in wettability and dissolution rate of ZMP. XRD studies proved that the amorphous ZMP-PVP K30 solid dispersions was formed only at the 1:5 drug to PVP weight ratio. This formulation was found to show a significant improvement in terms of the drug release with complete release of drug compared to physical mixtures and other formulations. So this amorphous solid dispersions may be useful for further to formulate dosage form. Keywords: Solid dispersion, Zolmitriptan, Urea, Polyvinyl Pyrrolidone K-30, PEG-6000, Dissolution Studies.